Pastoral systems dominated by fodder crops harvesting and grazing - Talamuci P.; Pardini A. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
In the Mediterranean environments, native pastures, directly influenced by climatic constraints, show a very high productive instability and this imply the necessity of an appropriate combination with forage crops and other resources, thus valorizing the existing contrasts, according with the wide variability of natural and socio-economic conditions. After a reminder on different typologies of pastoral systems, this paper presents a review on systems including fodder crops and sown or oversown pastures destined to harvesting or grazing. In the frame of the regularization of forage production calendar, the role and the genetic and agronomic control of different 'strategic' resources, particularly perennial and annual legumes, are considered. The possibilities of their combination at crop, farm and territory level in order to implement and manage conventional and non conventional systems are discussed. Pasture-woody resources relationships in view of a multi-use of territory are also presented. Finally, the research requirements and perpectives on this subject are considered.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)